Sacubitril/Valsartan Reduces Fibrosis and Alleviates High-Salt Diet-Induced HFpEF in Rats - Zhang, Wenchao; Liu, Jianwei; Fu, Yang; Ji, Huifang; Fang, Zheyan; Zhou, Wanming; Fan, Huimin; Zhang, Yingxuan; Liao, Yan; Yang, Ting; Wang, Xiaolin; Yuan, Wanwan; et al. (Frontiers in Pharmacology, 2021)
Abstract Previous studies have confirmed the clinical efficacy of Sacubitril/Valsartan (Sac/Val) for the treatment of heart failure with reduced ejection fraction (HFrEF). However, the role of Sac/Val in heart failure with preserved ejection fraction (HFpEF) remains unclear. Sac/Val is a combination therapeutic medicine comprising sacubitril and valsartan that acts as a first angiotensin receptor blocker and neprilysin inhibitor (ARNI). Here, we investigated the role of Sac/Val in high salt-diet induced HFpEF coupled with vascular injury as well as the underlying mechanism. Rats were fed with high-salt feed, followed by intragastric administration of Sac/Val (68 mg/kg; i.g.). The results of functional tests revealed that a high-salt diet caused pathological injuries in the heart and vascular endothelium, which were significantly reversed by treatment with Sac/Val. Moreover, Sac/Val significantly decreased the levels of fibrotic factors, including type I and type Ⅲ collagen, thus, reducing the ratio of MMP2/TIMP2 while increasing Smad7 levels. Further investigation suggested that Sac/Val probably reversed the effects of high-salt diet induced HFpEF by inhibiting the activation of the TGF-β1/Smad3 signaling pathway. Thus, treatment with Sac/Val effectively alleviated the symptoms of high-salt diet induced HFpEF, probably by inhibiting fibrosis via the TGF-β1/Smad3 signaling pathway, supporting the therapeutic potential of Sac/Val for the treatment of HFpEF.